Bariery wdrażania controllingu w systemach wynagrodzeń - Parkitna, Agnieszka; Górski, Arkadiusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The idea of the system Motivation's of Remuneration in Controlling was presented. The factors formation of system Motivation's of Remuneration in Controlling was describe. The type of system Motivation's of Remuneration in Controlling was presented. The base and the attribute Motivation's of Remuneration in Controlling was pointed. Barriers initiating controlling to systems of Remuneration was identified. Injunction to proper initiating was specified. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 318-325